Ujaran Kebencian Dan Perundungan di Dunia Maya: Tantangan Etika dalam Ruang Digital Indonesia - Riska Farwati; Wulan Yuliyanti; Wahyu Puji Rahayu Ningsih (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2023)
Globalization and technological advances are challenges for everyone. Indonesia is not only witnessing extraordinary advances in information technology, but also facing serious ethical challenges in the digital space. The two main problems that arise in this context are Hate Speech and Cyberbullying. These two phenomena have become increasingly disturbing issues and require serious attention from society, government and related institutions. This research uses a literature study method through scientific journals and books. In some cases, hate speech can even encourage acts of physical violence against the targeted group. With these technological advances come significant ethical challenges. The importance of ethics in the digital space cannot be ignored. Digital ethics education is key to building a deep understanding of how to behave well in the digital world. Because there are also laws that regulate these two phenomena.